2021
DOI: 10.3389/fphys.2021.585895
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Sensing Receptor Contributes to Hyperoxia Effects on Human Fetal Airway Smooth Muscle

Abstract: Supplemental O2 (hyperoxia), necessary for maintenance of oxygenation in premature infants, contributes to neonatal and pediatric airway diseases including asthma. Airway smooth muscle (ASM) is a key resident cell type, responding to hyperoxia with increased contractility and remodeling [proliferation, extracellular matrix (ECM) production], making the mechanisms underlying hyperoxia effects on ASM significant. Recognizing that fetal lungs experience a higher extracellular Ca2+ ([Ca2+]o) environment, we previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
(126 reference statements)
1
1
0
Order By: Relevance
“…In ASM, calcium release from the sarcoplasmic reticulum drives cellular contraction, and calcium exchange between the mitochondrion and sarcoplasmic reticulum is important for regulating contraction as well as other cellular functions, including ATP production from oxidative phosphorylation and subsequent ROS production [ 70 , 78 ]. Our data showing increased oxidative damage and altered mitochondrial morphology in response to various O 2 conditions or antioxidants build on our previously published work showing increased intracellular calcium response to agonists in human fASM exposed to hyperoxia [ 79 ]. It is now worth investigating whether ROS can be targeted to help mitigate elevated [Ca 2+ ] i in various O 2 conditions.…”
Section: Discussionsupporting
confidence: 84%
“…In ASM, calcium release from the sarcoplasmic reticulum drives cellular contraction, and calcium exchange between the mitochondrion and sarcoplasmic reticulum is important for regulating contraction as well as other cellular functions, including ATP production from oxidative phosphorylation and subsequent ROS production [ 70 , 78 ]. Our data showing increased oxidative damage and altered mitochondrial morphology in response to various O 2 conditions or antioxidants build on our previously published work showing increased intracellular calcium response to agonists in human fASM exposed to hyperoxia [ 79 ]. It is now worth investigating whether ROS can be targeted to help mitigate elevated [Ca 2+ ] i in various O 2 conditions.…”
Section: Discussionsupporting
confidence: 84%
“…We previously established a model of moderate hyperoxia exposure in neonatal mice (Bartman et al., 2024 ; Faksh et al., 2016 ; Roesler et al., 2021 ; Vogel et al., 2019 ; Wang et al., 2014 ). Briefly, newborn mouse pups (postnatal day 0, P0) are exposed to either 21% O 2 (room air) or 50% O 2 (moderate hyperoxia chamber) from P0‐P7.…”
Section: Resultsmentioning
confidence: 99%
“…Studies show that altered airway structure and function in neonates contributes to childhood asthma: children less than 3 years old with thickened airways display recurrent wheeze prior to the emergence of pediatric asthma (Baldwin & Roche, 2002 ; O'Reilly et al., 2013 ; Saglani et al., 2007 ). Additionally, in vitro studies using human fetal ASM exposed to moderate O 2 show increased intracellular calcium, proliferation, extracellular matrix deposition, and cellular senescence (Britt Jr. et al., 2015 ; Hartman et al., 2012 ; Parikh et al., 2018 ; Roesler et al., 2021 ). Similarly, in vivo studies using a neonatal mouse model of moderate hyperoxia exposure show increased ASM thickness, collagen deposition, AHR following methacholine (MCh) challenge, and sex differences in response to O 2 (Bartman et al., 2024 ; Faksh et al., 2016 ; Wang et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies using human fetal airway smooth muscle have shown dose-dependent effects with moderate oxygen increasing proliferation and higher levels (>60%) driving apoptosis ( 102 ). Furthermore, studies on human fetal airway smooth muscle have shown moderate hyperoxia increases airway hyperreactivity via intracellular calcium response to bronchoconstrictor agonists ( 102 , 142 , 143 ). In vivo studies using moderate hyperoxia in a neonatal mouse model have demonstrated structural and functional changes similar to those seen in asthma and reactive airway disease: increased airway hyperreactivity in response to methacholine challenge as well as increased ASM thickness and collagen deposition in the airway ( 100 , 132 ).…”
Section: Oxygen and Pediatric Airway Diseasementioning
confidence: 99%